A inserção dos tratados internacionais de direitos humanos na Constituição brasileira: uma perspectiva sobre a proteção da dignidade da pessoa humana - Tozo, Ricardo Rodrigo Marino (2015)
The present study aims to delineate the trajectory and the construction of Human Rights for the consequent need to materialize them in International Human Rights Treaties. From an international legal perspective solidified in the Treaties, the work seeks to evaluate the theories of reception and jurisdictionalization the Brazilian legal system, from the viewpoint of the principle of human dignity